Launching Europe : An Ethnography of European Cooperation in Space Science - Zabusky, Stacia E. (Book collections on Project MUSE., 2011)
In this first ethnographic study of the European Space Agency, Stacia Zabusky explores the complex processes involved in cooperation on space science missions in the contemporary context of European integration. Zabusky argues that the practice of cooperation does not depend on a homogenizing of interests in a bland unity. Instead, it consists of ongoing negotiation of and conflict over often irreconcilable differences. In this case, those differences are put into play by both technical and political divisions of labor (in particular, those of big science and of European integration). Zabusky s.